Radioprotective efficacy of dipyridamole and AMP combination in fractionated radiation regimen, and its dependence on the time of administration of the drugs prior to irradiation - Hofer, M; Pospísil, M; Netíková, J; Znojil, V; Vácha, J; Holá, J (Physiological research, 1995)
We have recently demonstrated that the combined administration of dipyridamole and adenosine monophospate to mice induces radioprotective effects in terms of postirradiation haemopoietic recovery in animals irradiated with a single dose. The aim of the present experiments was to investigate the radioprotective ability of the drug combination under conditions of fractionated radiation treatment. It has been shown that administration of drugs either 15 or 60 min before each of the five daily 3-Gy doses of gamma-radiation enhances haemopoietic recovery and survival of mice exposed to an additional "top-up" dose of 3.5 Gy. Furthermore, it has been ascertained that the regimen using administration of the drugs 60 min prior to irradiation is more effective than administration of the drugs 15 min prior to irradiation. Due to the evidence that administration of the drugs 15 min prior to irradiation protects the organism mainly via mechanisms of systemic hypoxia while the pretreatment 60 min before irradiation avoids the role of hypoxia and mainly induces cell proliferation effects, our results suggest a more effective protective role of mechanisms stimulating haemopoiesis under conditions of fractionated radiation. The data may provide a basis for more rational use of radioprotection in fractionated radiation regimens.
Keywords: buněčné dělení; tělesná hmotnost; kombinovaná farmakoterapie; Drug Therapy, Combination; Mice; Adenosine Monophosphate; zvířata; Hypoxia; hypoxie; Time Factors; vazodilatancia; Dipyridamole; mužské pohlaví; Organ Size; adenosinmonofosfát; radioprotektivní látky; Drug Administration Schedule; časové faktory; Radiation-Protective Agents; Hematopoietic System; myši; rozvrh dávkování léků; Animals; Vasodilator Agents; velikost orgánu; Mice, Inbred C57BL; Body Weight; hematopoetický systém; analýza přežití; Male; dipyridamol; Cell Division; Survival Analysis; myši inbrední C57BL